SISTEM SUBGROUND PASSIVE COOLING PADA GEREJA DI CIBUNUT, KUNINGAN, JAWA BARAT - Inggit Musdinar Sayekti Sihing Yang Mawantu; Sri Kurniasih (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Abstract: Subground passive cooling is a passive cooling technique that is carried out by flowing cold air in the ground into the room. The Pasio Christi Church in Cibunut, Kuningan, West Java was founded in 1965. Then the church implemented a passive cooling subground system through renovations carried out on May 11, 2018. This passive cooling system is usually carried out in areas with subtropical to cold climates, however Cibunut who has a tropical climate tries to implement this system. In fact, there is concern if the system is implemented in the tropics, such as humidity entering the system, causing fungal problems that can have an impact on health. . Therefore this research describes the application of the subground passive cooling system in tropical climates with the following steps: (i) data collection in the form of literature studies, (ii) identification of the subground passive cooling system of Cibunut Church, (iii) elaboration of theory regarding subground passive cooling, (iv) analysis of the application of subground passive cooling of the Cibunut church with the results of theoretical elaboration. This research is expected to be able to contribute in science, especially regarding the application of subground passive cooling systems in tropical climates.Abstrak: Subground passive cooling merupakan teknik pendinginan pasif yang dilakukan dengan mengalirkan udara dingin dalam tanah ke dalam ruangan. Gereja Pasio Christi di Cibunut, Kuningan, Jawa Barat didirikan sejak 1965. Lalu gereja ini menerapkan sistem subground passive cooling melalui renovasi yang dilakukan pada 11 Mei 2018. Sistem pendinginan pasif ini biasanya dilakukan pada wilayah dengan iklim subtropis hingga iklim dingin, namun demikian Cibunut yang beriklim tropis mencoba untuk menerapkan sistem ini. Padahal ada kekawatiran jika sistem ini diterapkan di wilayah tropis, seperti kelembaban yang masuk dalam sistem sehingga muncul permasalahan jamur yang dapat berdampak pada kesehatan. Oleh karena itu pada penelitian ini mendiskripsikan mengenai penerapan sistem subground passive cooling pada wilayah beriklim tropis dengan langkah-langkah sebagai berikut : (i) pengumpulan data dalam bentuk studi literatur, (ii) identifikasi sistem subground passive cooling Gereja Cibunut, (iii) elaborasi teori mengenai subground passive cooling, (iv) analisis penerapan subground passive cooling gereja Cibunut dengan hasil elaborasi teori. Dari penelitian ini diharapkan mampu memberikan sumbangsih dalam keilmuan terutama mengenai penerapan sistem subground passive cooling pada wilayah beriklim tropis.